Theologische hermeneutiek en de postmoderne uitdaging - Willem J. Ouweneel (Acta Theologica)
Some theologians have reacted negatively to the postmodern challenge (Wells, Groothuis), others more positively (McGrath, Thiselton, Vanhoozer, Grenz). The latter have taken up Ricoeur’s concept of the “masters of suspicion” (Marx, Nietzsche, Freud), i.e., suspicion with respect to the motives behind, and the functions of, our views. Foucault and Lyotard have pointed out the social circumstances, power games, mental self-deception and prejudices that play a role in our views. I assert that, basically, all these insights were anticipated by the Christian philosopher Herman Dooyeweerd, so that he may be called the “master of suspicion” par excellence. Theological hermeneutics has gained more importance nowadays than ever before. It is therefore essential to recognise it as basically of a philosophical nature. This underlines again the necessity of a Christian-philosophical framework for doing responsible theology. In this respect, Dooyeweerd is not outdated; on the contrary, he has anticipated many of the present hermeneutical developments.